2000
DOI: 10.1101/gr.10.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping Suggests that the Goat Polled Intersex Syndrome and the Human Blepharophimosis Ptosis Epicanthus Syndrome Map to a 100-kb Homologous Region

Abstract: To clone the goat Polled Intersex Syndrome (PIS) gene(s), a chromosome walk was performed from six entry points at 1q43. This enabled 91 BACs to be recovered from a recently constructed goat BAC library. Six BAC contigs of goat chromosome 1q43 (ICC1–ICC6) were thus constructed covering altogether 4.5 Mb. A total of 37 microsatellite sequences were isolated from this 4.5-Mb region (16 in this study), of which 33 were genotyped and mapped. ICC3 (1500 kb) was shown by genetic analysis to encompass the PIS locus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Fine-mapping studies suggested that both PIS (on 1q43) and the human blepharophimosis ptosis epicanthus syndrome (BPES) (on 3q23) loci mapped to a 100-kb homologous region. [15] The PIS mutation has been characterized and involves a small deletion (probably removing regulatory elements) that leads to a misregulation of several genes in the region. [16] More or less at the same time, mutations in the gene FOXL2 were shown to be responsible for BPES.…”
Section: Foxl2: a Molecular Actor In The Spotlightmentioning
confidence: 99%
“…Fine-mapping studies suggested that both PIS (on 1q43) and the human blepharophimosis ptosis epicanthus syndrome (BPES) (on 3q23) loci mapped to a 100-kb homologous region. [15] The PIS mutation has been characterized and involves a small deletion (probably removing regulatory elements) that leads to a misregulation of several genes in the region. [16] More or less at the same time, mutations in the gene FOXL2 were shown to be responsible for BPES.…”
Section: Foxl2: a Molecular Actor In The Spotlightmentioning
confidence: 99%
“…The mapping has subsequently been refined and, by haplotype analysis, the mutation localized to one BAC (376H9, Fig. 3) which has been partially sequenced (Vaiman et al, 1999;Schibler et al, 2000). By sequence comparison between horned (PIS +/+ ) and sex-reversed (PIS -/-) animal DNAs, the mutation was found to be an 11.7-kb deletion encompassing no known coding sequences (Pailhoux et al, 2001b).…”
Section: Quest For the Pis Mutationmentioning
confidence: 99%
“…Once the PIS mutation had been limited to one BAC (Schibler et al, 2000), different strategies were developed in order to isolate putative transcribed regions in this DNA fragment. Out of the 20 putative exons tested, only PISRT1 has shown a dimorphic expression pattern in the gonads with higher levels in the ovaries compared to testes during fetal life (Pailhoux et al, 2001b).…”
Section: Pis Is a Transcriptional Regulatory Regionmentioning
confidence: 99%
“…Furthermore, a strong linkage disequilibrium among unrelated animals was detected with the two central markers of this region, suggesting a probable location for PIS in a ∼100 kb DNA region contained in one BAC (376H9). High resolution comparative mapping with human data shows that this DNA segment is the homologue of the human region associated with Blepharophimosis Ptosis Epicanthus inversus Syndrome, BPES [12]. This finding suggests that a homologous gene(s) could be responsible for the pathologies observed in humans and goats.…”
Section: Linkage Analysis Of the Pis Mutationmentioning
confidence: 81%